Comparison of daily and monthly results of three evapotranspiration models in tropical zone: a case study - Saghravani, Seyed Reza; Mustapha, Sa'ari; Ibrahim, Shaharin; Randjbaran, Elias (Science Publications, 2009)
Problem statement: Evapotranspiration (ET) has crucial role in agricultural activity, water management and hydraulic engineering. Recently many forms of the equation have been applied for estimating daily and monthly evapotranspiration around the world. Approach: In this study, the daily and monthly ET was estimated by Penman, Penman-Monteith (P&M) and Hargreaves equation to evaluate general relationships for estimating monthly and daily values of these 3 methods and also effect of different parameters such as Humidity and wind speed on fluctuation of ET. Results: The results showed that maximum and minimum values were belonging to Hargreaves and P&M models, respectively. Conclusion: Statistical analysis showed significant difference among the three methods and coefficient variant for daily and monthly analysis was 18.49 and 7.17 respectively. However, the difference between mean value of P&M and Hargreaves, that has the most different, is 1 mm year−1.